PERAN ZAKAT DAN INFAK TERHADAP PENDIDIKAN MUSTAHIK DI KOTA DEPOK - YUSUP, YUSUP; TANJUNG, HENDRI; AYUNIYYAH, QURROH (Kasaba, 2022)
This research aims to analyze the role of zakat and infaq on mustahik education in Depok City by focusing on the Zakat Success Amil Zakat Institution (LAZ). This research uses a qualitative method with a case study approach. Data obtained through interviews with LAZ Zakat Success administrators, observation and documentation. The results of this research also show that LAZ Zakat Sukses has distributed zakat and infaq funds for educational programs such as remote caregivers, scholarships, open high schools, educational assistance for state children, school equipment assistance, Wisma Achievement, and tahfidz houses. These programs have helped mustahik access education and improve their quality of life. This research concludes that zakat has an important role in improving the quality of mustahik education in Depok City. LAZ Zakat Sukses has succeeded in managing and distributing zakat and infaq funds for educational programs that have a positive impact on mustahik.